(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The purpose of this article is to formulate an analysis of the figure of the victim in the brazilian criminal process, as well as the contours and limits of their actions, notably with regard to the non-criminal prosecution agreement provided for in art. 28-A of the Criminal Process Code. To this end, an analysis of victimology and the issues that deal with the topic in the current legal system is carried out. It soughts to delimit the offended party’s sphere of action and highlight their importance and role as a subject of rights within the scope of negotiations, questioning which way would be most effective for their participation in identifying reparation for the damage. With this in mind, through a bibliographical review methodology, it is proposed to expand its scope of action, including within the scope of Restorative Justice, aiming to pay special attention to the functions of repression and prevention of punishment, without losing sight of the protagonism of Public Prosecutor’s Office, which is the legitimate party and holder of the criminal action to develop negotiations and effectively propose the agreement. In this context, the aim is to identify the place of the victim in the negotiations and their role.